THE FACTOR OF PREVENTING AMORALISM IN THE TASAVVUF PATH OF SELF-DEVELOPMENT THROUGH ETHICAL EDUCATION OF INDIVIDUALS - Komilov Ro‘zi Rabiyevich; Afanasyeva Olesya Gennadyevna (Bright Mind Publishing, 2025)
If we analyze the teachings of Sufi masters, we can see that lust (amoralism) puts people away from God. It leads to corruption and creates a barrier for those who only think about their personal benefits. Once someone is under the influence of lust, they cannot find contentment in anything, even if they have to resort to illegitimate and forbidden means. In the end, they become cruel, merciless, and hypocritical.
Keywords: Sufism, lust, ethics, happiness, virtue, amoralism, specialization, selfishness, corruption, cause.